Neuroendocrine regulation of secretogranin-II (SgII) expression in the goldfish pituitary. - Samia, Marwan. (University of Ottawa (Canada), 2002)
Secretogranin-II (SgII) is a secretary protein involved in the regulated secretory pathway of endocrine and neural cells. Preliminary evidence has suggested a role for it in reproductive function. The objectives of our studies were to elucidate how SgII expression is regulated within the goldfish reproductive system in an attempt to shed some light on its possible actions. Goldfish are a seasonally reproducing species with an annual cycle. The pituitary SgII expression levels fluctuate with the reproductive cycle. Sex steroids are not directly responsible for the cyclicity of SgII expression, nor do they regulate it at any time of the year. On the other hand, gonadotropin-releasing hormone (GnRH), the principal stimulatory factor of the reproductive system upregulates SgII expression. Testosterone suppresses the stimulatory effect of GnRH at certain stages of the reproductive cycle. Many other studies are necessary to fully comprehend the regulation of SgII within the reproductive system and whether it has any concrete functions therein.
Keywords: Biology, Neuroscience.